From Gamma Coherence to Theta-Phase Synchronization: Task-Dependent Interhemispheric Integration in Boundary-Free Multiple-Object Tracking - Yunfang Xu; Xiaoxiao Yang; Zhengye Si; Meiliang Liu; Zijin Li; Xinyue Yang; Zhiwen Zhao (Brain Sciences, 2025)
Background: Multiple-object tracking (MOT) is a cognitively demanding task involving sustained attention and interhemispheric integration. While previous studies have revealed that gamma-band coherence mediates interhemispheric integration in MOT tasks with visible internal boundaries, the neural mechanisms supporting integration without such boundaries remain unclear. This study investigated brain functional connectivity during a boundary-free MOT task. Methods: Thirty-eight healthy participants completed the task under four experimental conditions, defined by two load levels (two and four targets) and two movement configurations (within hemifield and between hemifield). Electroencephalography (EEG) activity was recorded in both the task and resting states. The phase locking value (PLV) and network properties were analyzed. Results: The behavioral results demonstrated greater accuracy under the two-target conditions than under the four-target conditions and significantly worse performance under the four-target between-hemifield condition. EEG analyses revealed increased theta-band PLV under the four-target between-hemifield condition, reflecting enhanced interhemispheric synchronization. The PLV difference between the four-target within-hemifield and between-hemifield conditions was positively correlated with the accuracy difference, suggesting that increased theta-band phase synchronization is associated with better task performance. Moreover, sex-related differences were observed, with males showing better performance, shorter click times, and higher theta-band PLV than females. Conclusions: Our study provides evidence that theta-band phase synchronization plays a critical role in interhemispheric integration during boundary-free MOT, extending previous findings on gamma-band coherence under visible-boundary conditions and offering new insights into the neural mechanisms of interhemispheric coordination.